2012
DOI: 10.1038/hdy.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and reducing AFLP genotyping error: an example of tradeoffs when comparing population structure in broadcast spawning versus brooding oysters

Abstract: Phylogeographic inferences about gene flow are strengthened through comparison of co-distributed taxa, but also depend on adequate genomic sampling. Amplified fragment length polymorphisms (AFLPs) provide a rapid and inexpensive source of multilocus allele frequency data for making genomically robust inferences. Every AFLP study initially generates markers with a range of locus-specific genotyping error rates and applies criteria to select a subset for analysis. However, there has been very little empirical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…By using theses loci in further analyses much of the genomic diversity that exists within the dataset is lost. Previous studies have demonstrated that larger datasets having higher error rate can yield greater information than a small number of loci with little error [7]. This reduction in information content may be related to the reduction of loci with moderate allele frequencies, as a result of using fixed error rate thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using theses loci in further analyses much of the genomic diversity that exists within the dataset is lost. Previous studies have demonstrated that larger datasets having higher error rate can yield greater information than a small number of loci with little error [7]. This reduction in information content may be related to the reduction of loci with moderate allele frequencies, as a result of using fixed error rate thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated inaccurate population substructure patterns in both datasets with high genotyping error rates and datasets using selected loci with very low error rates [7]. These results suggest that a tradeoff exists between reducing error rate and maintaining loci with high information content.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…; Holland et al . ; Zhang & Hare ). Detailed reviews of how genotyping error can be generated are provided by Bonin et al .…”
Section: Introductionmentioning
confidence: 99%
“…). For example, Zhang & Hare () compared the results obtained from AFLP data sets varying in error rates (0, 1, 2, 3, 4 and >4%) and found that inaccurate inferences of a previously determined phylogeographic pattern were made based on data sets with >4% error. While it is possible that genotyping errors may not significantly bias overall conclusions (e.g.…”
Section: Introductionmentioning
confidence: 99%